Changing Threat Perceptions and Military Doctrines - Valki, Laszlo. author. aut Link
XIII, 257 p.
Keywords: Owing to the revolutionary changes in Eastern Europe and the Soviet Union, the threat perceptions of the East and West have vanished. The contributors to this volume report this social process and try to identify some of the new threat perceptions which will arise.